Features and Functions of Supreme Audit Institutions - Stapenhurst, Rick (World Bank, Washington, DC, 2012)
Supreme audit institutions are national agencies responsible for auditing government revenue and spending. Their legal mandates, reporting relationships, and effectiveness vary, reflecting different governance systems and government policies. But their primary purpose is to oversee the management of public funds and the quality and credibility of governments' reported financial data. In the past the World Bank and other donors often established parallel auditing systems for their projects, undermining developing countries' supreme audit institutions, on whose work they could not always rely. Equally problematic have been projects that encouraged performance auditing but ignored basic weaknesses in financial management. In recent years the Bank has tried to strengthen oversight agencies such as supreme audit institutions. This note is intended to help Bank staff appreciate the role and nature of these institutions, particularly in managing public spending, ensuring financial accountability, and strengthening public institutions.